2018
DOI: 10.1016/j.clbc.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Palbociclib Combinations in Hormone Receptor–Positive Metastatic Breast Cancer Patients After Prior Everolimus Treatment

Abstract: There is a limited clinical activity of palbociclib combinations after progression with everolimus combination therapy. Further studies are necessary to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 14 publications
4
21
1
Order By: Relevance
“…These data are consistent with previous reports of in vitro studies that show CDK4/6 inhibitors can reverse acquired resistance to inhibitors of PI3K [36]. Data from two clinical studies with small numbers of patients indicate that palbociclib-based therapies have limited efficacy after progression on the mTORC1 inhibitor everolimus (RAD001) [37,38]. However, the efficacy of CDK4/6 inhibition post-progression on PI3K inhibitor-based therapies is yet to be investigated.…”
Section: Discussionsupporting
confidence: 90%
“…These data are consistent with previous reports of in vitro studies that show CDK4/6 inhibitors can reverse acquired resistance to inhibitors of PI3K [36]. Data from two clinical studies with small numbers of patients indicate that palbociclib-based therapies have limited efficacy after progression on the mTORC1 inhibitor everolimus (RAD001) [37,38]. However, the efficacy of CDK4/6 inhibition post-progression on PI3K inhibitor-based therapies is yet to be investigated.…”
Section: Discussionsupporting
confidence: 90%
“…In the whole population, we found that patients who had been treated with everolimus had signi cantly worse DCR (50.0%) and PFS (3.4 months) than everolimus-naïve patients. This nding appears to be consistent with that of a retrospective study of 23 patients in the United States (18). In that study, Dhakal et al found that palbociclib-based therapy had a DCR of 17.4% and a median PFS of 2.9 months in patients with metastatic breast cancer pretreated with everolimus (18).…”
Section: Discussionsupporting
confidence: 86%
“…Finally, combined targeting of CDK4/6 and PI3K pathways resulted in greater tumour regression compared with PI3K or CDK4/6 inhibition alone; and triplet therapy with CDK4/6 and PI3K inhibitors was more effective than dual therapy with respect to tumour regression (O'Brien et al 2014, Herrera-Abreu et al 2016. In two recent studies, cohorts of heavily pre-treated patients who had received everolimus obtained limited benefit from the addition of palbociclib, suggesting that CDK4/6 inhibitors should be used prior to or concurrently with drugs targeting the PI3K pathway (Dhakal et al 2018, du Rusquec et al 2018. The multiple types of PI3K inhibitors in clinical development, combined with the three lead CDK4/6 inhibitors, multiple classes of ER-directed therapies, and next generation selective ER degraders, in different lines of therapy, have resulted in a large number of combinations and permutations, creating a challenge when determining the optimal therapeutic strategy for a given patient.…”
Section: Strategies To Avert and Overcome Cdk4/6 Inhibitor Resistancementioning
confidence: 99%